Emancipated - Reyes, M. G. (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2015)
Legally liberated from parental control for different reasons, six teenagers share a house in Venice Beach, acting as a family, while harboring dangerous secrets.
Keywords: Teenagers -- Juvenile fiction; Roommates -- Juvenile fiction; Secrecy -- Juvenile fiction; Teenagers -- Fiction; Roommates -- Fiction; Secrecy -- Fiction; Los Angeles (Calif.) -- Juvenile fiction; Los Angeles (Calif.) -- Fiction